Voltammetric determination of cholecalciferol at glassy carbon electrode performed in water-ethanol mixture - Nallbani, Arlinda; Holubová, Julie; Sýs, Milan; Tahir, Arbneshi; Vytřas, Karel (My University, 2018)
To confirm or disprove previous hypotheses, cyclic voltammetry of 0.5 mM cholecalciferol (vitamin D3) at glassy carbon electrode (GCE) and platinum disk electrode (PtE) in pure acetonitrile and water-ethanol mixture at 50 mV·s-1 has been used to investigate the oxidation mechanism. The oxidation occurs in two one-electrone steps. According to calculation of the highest electron density in cholecalciferol molecule which is evidently delocalized over carbon atoms of the three conjugated double bonds (C19, C10, C5-C8) points to part of the molecule involved in oxidation processes. An oxidation peak (at +0.925 V vs. Ag/AgCl) was used to develop direct voltammetric method based on differential pulse voltammetry for the vitamin D3 determination at GCE performed in 40% ethanol containing 0.1 M LiClO4. Under optimization of analytical procedure, it was found that a composition of the supporting electrolyte used significantly affects a current response of oxidation peak obtained. Satisfactory sensitivity was achieved in the 1:1 water-ethanol mixture containing 0.05 M lithium perchlorate as as supporting electrolyte. The linear range for vitamin D3 determination was 2.4 × 10−6 – 3.5 × 10−4 M with the detection limit of 8.0 × 10−7 M. This work demonstrates a fact that the GCE is suitable electroanalytical device for analysis of various food supplements and medicaments.
Voltametrické stanovení cholekalciferolu pomocí elektrody ze skelného uhlíku v prostředí vodně-ethanolické směsi
Keywords: Cholecalciferol; anodic differential pulse voltammetry; glassy carbon electrode; vitamin food supplements; Cholekalciferol; anodická diferenčně pulzní voltametrie; elektroda ze skelného uhlíku; vitamínové doplňky stravy